ECONOMIC GROWTH OF THE AGRICULTURAL SECTOR OF MOLDOVA COMPARED TO CENTRAL AND EASTERN COUNTRIES OF EUROPE - Aliona SARGO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2014)
The main opportunities for the development of the national economy of the Republic of Moldova are closely related to the development of the agricultural sector. The agricultural sector remains a priority for Moldova because 30% out of the population are employed in this area, 75% of the country surface is agricultural land, and agriculture holds 13% of GDP. With these indicators, the agricultural sector can not be neglected. Undoubtedly our main effort should be directed towards the recovery of agriculture and increase the living standards of people from rural areas. It is necessary to review the huge opportunities for agricultural growth and rural areas by using both adequate investments and updating rural development strategies. Agriculture remains one of the most important sectors with huge possibilities and an unjustly neglected sectors.